Stereotip Warga Tionghoa Dalam Geopolitik Hubungan Indonesia dengan Tiongkok - Taufik Hidayadi; Henny Saptatia Drajati Nugrahani (Muqoddima Jurnal Pemikiran dan Riset Sosiologi, 2020)
China’s very rapid development has implications for regional relations in the region. Indonesia has made a false evaluation and calculation from a geopolitical and geostrategic point of view which is applied as a national policy and resilience. The most rational consideration of a free and active foreign policy is with the bilateral relations between Indonesia and China, not only in an ordinary partnership but more in close relations which have economic and technological implications. The geopolitical conditions in the dynamic relationship between Indonesia and the People’s Republic of China can be seen in the investment economic cooperation where the People’s Republic of China is one of the four largest investors in Indonesia in the last five years. The South China Sea polemic and the Covid-19 pandemic that originated in Wuhan China also further added to the dynamics of the relationship. The relationship between Indonesia and the People’s Republic of China has been ready to ebb and flow since the recognition of the establishment of the People’s Republic of China in 1949, experiencing events such as the dual citizenship agreement, fluctuations in political ideology from the Old Order to the New Order, and state policies towards ethnic Chinese after that. Policies such as assimilation based on stereotypes towards the Chinese ethnic group have left wide gaps in the relationship between the state and its population as well as the attitude of the Indonesian people towards ethnic Chinese was clearly seen during the 1998 reformation, event appears not yet finished in resolving the problem, as seen in the 2017 DKI Jakarta Pilkada.